A Web-Based Student Housing Assistant Model - Hamed, Zyad Adnan (2010)
The World Wide Web presents a global access to an extensive scope of data for a huge number of consumers at the present. It turned out to be the most significant service of the Internet lately. University Utara Malaysia (UUM) is one of the leading public universities in Malaysia. It attracts student from many different countries. We found out after interviewing many international students that they have had many difficulties when they searched for accommodation. This project aims to propose a model of a Web-Based Student Housing Assistant that can be adopted by UUM to be used by the international students in order to help them to find places to stay during their studies. The developed prototype which is named UUM Housing Assistant has been evaluated using TAM based questionnaire. The results of the questionnaire confirmed that the users of the system were pleased and satisfied.